A sideways look at conservation and consistency in tourism policy. Issue 3 (1st March 2018) - Dickman, Amy; Packer, Craig; Johnson, Paul J.; Macdonald, David W.
Abstract : Article impact statement : Wildlife‐based land management should be based on consistent principles for promoting sustainability.